THE STUDY OF ANNEMARIE SCHIMMEL'S SPIRITUAL HERITAGE BY WORLD RESEARCH SCHOLARS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article highlights the study of the spiritual heritage of the German Islamic scholar Annemarie Schimmel by world researchers. Some parts of scientific research and scientific articles about the life and work of Annemarie Schimmel are analyzed and discussed, and appropriate conclusions are made.